Density, Distance and Division : The Case of Chongqing Municipality, China - Roberts, Mark (2012)
This paper analyses the empirical relevance of the 2009 World Development Report's 3D framework for the explanation of spatial productivity disparities within Chongqing municipality's non-primary sector. In doing so, it presents evidence of a significant role for distance in determining these disparities, especially within the municipality's Southeast wing. The evidence of a role for density is more mixed, however, with findings of agglomeration economies depending on the method of estimation used. These results have important policy implications both for the municipality itself and China overall.